SPEECH DISORDERS IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Manal Adel Makki, Prof .dr. ImadHussainObaid Al-Morshedy, Ass.prof . Jalal Aziz Farman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify phonological and linguistic disorders among children with autism spectrum disorder in the Imam Al-Hussein Center (P) in Babil Governorate for the academic year (2019-2020), and the basic sample was chosen intentionally, as the researcher adopted the descriptive approach to conduct the steps of the current research The sample consisted of (10) children, and after the researcher reviewed the studies and measures related to the subject of her research as she adopted the scale (Aleemat, 2009), the logical dimension consisting of (68) items and after extracting the psychometric properties from (honesty and consistency) was applied to the sample the basic,After the data was emptied for the purpose of extracting the results, it was statistically processed using a number of statistical methods, including the T-test for one sample. They have speech disorders.